Pelatihan Konselor Sebaya untuk Meningkatkan Pengetahuan Mengenai Keterampilan Dasar Konseling Agen Kesehatan Mental di Perguruan Tinggi - siska oktari; Dwi Puspasari; Sabrina Puti Afifah; Salsabila Hanifa; Fauziatul Azimah (Universitas Andalas, 2024)
College students often encounter a range of emotional and academic challenges that can adversely affect their mental health. Peer counseling offers a promising approach to help students manage these difficulties and enhance their mental well-being. To maximize the effectiveness of peer counseling, it is crucial to develop and refine counseling microskill through targeted training. This study investigates the impact of peer counseling training on counseling the microskill of university students. Utilizing a quasi-experimental pretest-posttest design, the research involved 29 university students. Data were collected through both objective and subjective measures. Objective measures included cognitive test scores on counseling material, while subjective measures assessed participants' self-perceptions of their microskill. Results indicated a significant improvement in counseling microskill post-training, with objective and subjective measurements showing increased scores. The subjective analysis yielded a significance value of .000 (p<0.05) with a negative t-value of -12.345, while the objective analysis also showed significance at .000 (p<0.05) with a negative t-value of -10.822. These findings suggest that peer counseling training effectively enhances counseling microskill among university students.